ChemInform Abstract: Synthesis and Biophysical Properties of Constrained D‐Altritol Nucleic Acids (cANA). Issue 5 (4th February 2014) - Migawa, Michael T.; Prakash, Thazha P.; Vasquez, Guillermo; Seth, Punit P.; Swayze, Eric E.
Abstract Constrained altritol nucleotide derivatives (I) are incorporated into antisense oligonucleotides (ASO) in order to study how conformationally restricting the D‐altritol backbone‐containing ASO will affect their ability to form duplexes with RNA.